Implementasi Kredit Usaha Rakyat bagi Pelaku Usaha Mikro Kecil dan Menengah (UMKM) dan Realitas Praktik Rentenir - Manuhutu, Lonela; Maheswara, Giovanni Battista (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2024)
This study will explain the implementation of People’s Business Credit for Micro, Small and Medium Enterprises and explain the reasons why Micro, Small and Medium Enterprises actors prefer moneylenders to follow the People’s Business Credit program that has been provided by the government and the obstacles that are feared by the perpetrators. Micro, Small and Medium Enterprises if they participate in the People’s Businesss Credit program. This study aims to determine and examine the extent to which the implementation of People’s Business Credit reaches Micro, Small and Medium Enterprises and examines the interest of Micro, Small and Medium Enterprises to moneylenders compared to People’s Business Credit which is held by the government and has bank interest the smaller one.     This is an open-access article under the CC–BY 4.0 license.